2021
DOI: 10.1155/2021/6640324
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Knowledge and Practice of Breast Self-Examination among Female University Students, Gaza

Abstract: Breast cancer is the highest public detected cancer among female population in the majority of countries worldwide. Breast self-examination (BSE) is a useful screening tool to empower women and raise awareness about their breast tissues and help detect any breast abnormalities when they occur. This study aimed to assess the level of female university students’ knowledge and practice of BSE. A self-administered questionnaire was used to assess the knowledge about breast cancer and related items, and an observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 24 publications
6
44
2
3
Order By: Relevance
“…According to this study, 25% of the respondents mentioned that BSE should be performed every month, while 60 (14.7%) of the respondents indicated that BSE should be performed after menstruation. On the other hand, a study from the State of Palestine reported that almost 70% of the participants knew the right time to conduct BSE, which is a few days after menstruation [ 33 ]. About 56% of students in this study acknowledged BSE as a form of BC screening.…”
Section: Discussionmentioning
confidence: 99%
“…According to this study, 25% of the respondents mentioned that BSE should be performed every month, while 60 (14.7%) of the respondents indicated that BSE should be performed after menstruation. On the other hand, a study from the State of Palestine reported that almost 70% of the participants knew the right time to conduct BSE, which is a few days after menstruation [ 33 ]. About 56% of students in this study acknowledged BSE as a form of BC screening.…”
Section: Discussionmentioning
confidence: 99%
“…BSE is still recommended as a general method for increasing breast health awareness, which makes it easier for women to detect any changes that may arise [ 8 , 16 , 17 ]. Despite the benefits, many women in many countries do not perform regular self-breast checks [ 8 , 13 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits, many women in many countries do not perform regular self-breast checks [ 8 , 13 , 15 , 18 ]. Many women cited a lack of competence as the primary reason for not doing BSE [ 16 , 17 , 19 ]. For younger women, BSE education and adherence are a doorway to health-promoting behaviors, laying the groundwork for eventual adherence to clinical breast examination and mammography screening, if available [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female students were aware of breast cancer but had poor knowledge about signs and symptoms of breast cancer, whereas there was a lower rate of knowledge about performing breast self-examination [14].The Egypt study reported a moderate level of knowledge of breast cancer and its screening methods [15]. Despite having knowledge of various aspects of breast cancer such as risk factors, warning signs, and symptoms, they had little knowledge of screening methods and practised lower BSE [16].…”
Section: Introductionmentioning
confidence: 99%